How do unanticipated discoveries of oil fields affect the oil price? - Lisa Leinert (ETH Zurich, CER-ETH - Center of Economic Research, 2010)
The Hotelling rule argues that the price for a nonrenewable resource adjusts to the shadow value of the resource, reflecting the remaining availability of the resource. We empirically test the Hotelling rule on the effect of unanticipated oil field discoveries. We do not find evidence for a significant adjustment of the price of crude oil to news about greater resource availability and therefore conclude that the price for crude oil does not follow the theoretically optimal price path.
Keywords: Q31; Q41; G14; 330; Nonrenewable Resource; Oil Price; Exhaustible Resources; Information Acquisition; Erschöpfbare Ressourcen; Fossile Energie; Ölpreis; Erdölvorkommen; Hotelling-Regel; Theorie